Precarity as Resistance and Cultural Solidarity - Abdul Aziz Hafiz (PRISM)
This discursive paper uses the work of Freire and others to propose a critical pedagogy for precarity which is grounded in forms of radical (post)politics. A critical pedagogy for precarity is proposed that calls for a replacement of, or synthesis with, the UK government’s employability in HE agenda. Through the conscientisation of prospective graduates towards a ‘being-with-the-world’ and the associated mental habits and bodily practices that focus on the principles of a Social and Solidarity Economy (SSE), solidarity, reciprocity and sustainability, as a response to precarity, is possible by creating local solidarity-based associational spaces for critical education and praxis, we advocate for critical pedagogical practices alongside more opportunities for collective action that engender solidarity, reciprocity and sustainability in graduates’ bodily practices and modes of thinking and being, through a critical pedagogy that facilitates cultural action for freedom, self-help and collective forms of social provisioning of biological and social needs: housing, food, energy production, social caring and welfare needs in general.